First Reported Human Cases of Leptospirosis in the United States Virgin Islands in the Aftermath of Hurricanes Irma and Maria, September–November 2017. (5th June 2019) - Marinova-Petkova, Atanaska; Guendel, Irene; Strysko, Jonathan P; Ekpo, Lisa LaPlace; Galloway, Renee; Yoder, Jonathan; Kahler, Amy; Artus, Aileen; Hoffmaster, Alex R; Bower, William A; Walke, Henry; Ellis, Brett R; et al.
Abstract: Objective: Following Hurricanes Irma and Maria, the first case of human leptospirosis ever identified in the US Virgin Islands (USVI) was reported to the Virgin Islands Department of Health. Leptospirosis is a potentially fatal bacterial disease caused by Leptospira species found in animal urine and urine-contaminated water and soil. Outbreaks can occur following extreme weather events. Method: Additional cases of leptospirosis were identified in the 2.5 months post-hurricanes by reviewing emergency department (ED) records from territorial hospitals for patients demonstrating leptospirosis-consistent symptoms, testing symptomatic patients previously enrolled in the USVI arbovirus surveillance system (VIASS), and adding leptospirosis testing prospectively to VIASS. Available patient sera underwent local rapid diagnostic testing for anti- Leptospira IgM followed by confirmatory microscopic agglutination testing at the US Centers for Disease Control and Prevention. Water was collected from cisterns with epidemiologic links to confirmed cases and tested by real-time PCR (qPCR) for pathogenic Leptospira spp. Results: Sixteen retrospectively identified symptomatic patients were enrolled in VIASS; 15 with available samples tested negative. Based on review of 5226 ED charts, 6 patients were further investigated; of these, 5 were tested of which 1 was positive. Prospective leptospirosis surveillance tested 57 additional patients; of these, 1 was positive. Water from 1 of 5 tested cisterns was found positive by qPCR. Conclusions: This investigation documents the first 3 cases of leptospirosis reported in the USVI and demonstrates how VIASS successfully was adapted to establish leptospirosis surveillance. Contaminated cistern water was identified as a potential source for Leptospira spp. transmission, highlighting the need for additional post-hurricane remediation and disinfection guidance. Abstract : The detection of the first leptospirosis cases in the USVI after hurricanes indicates the need for enhanced leptospirosis surveillance following extreme weather events in tropical climates as well as the need for educational campaigns targeting key risk factors and prevention methods, including cistern contamination and disinfection.